INNOVATIVE PEDAGOGICAL ACTIVITY OF FUTURE HIGHER EDUCATION TEACHERS - Звєкова, Вікторія; Качуровська, Оксана (SWorldJournal, 2025)
The article explores the concept and essence of innovative pedagogical activity of future higher education teachers in the context of current educational transformations. The relevance of forming innovative competence as a key component of professional t